Internal, External, Networking Factors and Challenges of Small Medium Enterprise (SMES) Internationalization / Nur Zania Azurin Abdullah Sani, Ahmad Shazeer Mohamed Thaheer and Zahariah Mohd Zain - Abdullah Sani, Nur Zania Azurin; Mohamed Thaheer, Ahmad Shazeer; Mohd Zain, Zahariah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Internationalization procedure of small to medium-sized enterprises (SMEs) is part of the increasing economy. The study aims to identify relationships between the factors influencing the SMEs to internationalize and identifying the most impactful factor that affects the internationalization of SMEs. The factors affecting internationalization of SMEs identified were external, internal, networking as well as barriers and challenges. The study focusses on SMEs in the service sector in Klang Valley, Malaysia. The methods used to conduct the survey is by distributing the questionnaire through email. There are 100 selected SMEs in the service sector which are listed in SME Corp Malaysia website and MATRADE website. Regardless of whether the SME’s are practising international business or not, they will still be one of the potential respondents. The data were examined and obtained using the statistical software SPSS. The analysis used is reliability analysis, correlation analysis and regression analysis to meet the research objectives. The expected outcome from this research is to analyze the factors that will impact the internationalization of SMEs. The results of the analysis show that all the variables have a low positive correlation. The most influential factors that effects SMEs decision to go international are barriers and challenges.